颈动脉蹼的超声特征与缺血性卒中的The Relationship between Ultrasonographic Features of Carotid Web and Ischemic Stroke - 郭莉,宋欣同,张冠一,张倩,鞠奕,赵性泉(GUO Li, SONG Xintong, ZHANG Guanyi, ZHANG Qian, JU Yi, ZHAO Xingquan) (Zhongguo cuzhong zazhi)
目的 通过血管超声评估颈动脉蹼的结构特征并探究其与缺血性卒中的关系。 方法 回顾性连续纳入2021年1月—2024年6月就诊于首都医科大学附属北京天坛医院、经CTA确诊为颈动脉蹼且存在单侧颈动脉供血区缺血性卒中的患者。根据同侧颈动脉供血区缺血性卒中的发生情况，将患者分为同侧卒中组和对侧卒中组。通过血管超声测量颈动脉蹼长度、厚度、与管壁间夹角，记录颈动脉蹼的侧别、血管内位置、附着点、是否随血流飘动、是否顺血流方向及是否存在周围血栓等信息，比较两组患者颈动脉蹼的结构差异。 结果 本研究纳入102例颈动脉蹼患者，其中同侧卒中组70例，对侧卒中组32例。同侧卒中组患者肢体无力、运动障碍的发生率显著更高（54.3% vs. 34.4%，P=0.047），对侧卒中组则头痛更为常见（15.6% vs. 0，P=0.003）。超声结果提示同侧卒中组颈动脉蹼患者存在周围血栓的比例显著高于对侧卒中组（84.3% vs. 50.0%，P<0.001），但两组间颈动脉蹼的侧别、血管内位置、附着点、长度、厚度、与管壁间夹角、是否随血流飘动及是否顺血流方向方面的差异均无统计学意义（均P>0.05）。 结论 本研究发现颈动脉蹼患者存在周围血栓可能与同侧颈动脉供血区缺血性卒中的发生有关。 Abstract: Objective To evaluate the structural features of the carotid web by vascular ultrasound and explore the relationship with ischemic stroke. Methods This retrospective study consecutively enrolled patients with CTA-confirmed carotid web and unilateral carotid territory ischemic stroke at Beijing Tiantan Hospital, Capital Medical University from January 2021 to June 2024. Patients were divided into the ipsilateral stroke group and the contralateral stroke group based on the presence of ipsilateral ischemic stroke. Vascular ultrasound was used to measure carotid web length, thickness, and angulation relative to the vessel wall. Additional parameters, including laterality, location, attachment site, mobility with blood flow, orientation relative to flow direction, and presence of thrombosis around the carotid web were documented. Structural differences in carotid webs were compared between the two groups. Results This study enrolled 102 carotid web patients, with 70 in the ipsilateral stroke group and 32 in the contralateral stroke group. The incidence of limb weakness and motor impairment was significantly higher in the ipsilateral stroke group (54.3% vs. 34.4%, P=0.047), whereas headache was more frequently observed in the contralateral stroke group (15.6% vs. 0, P=0.003). Ultrasonographic findings demonstrated a significantly higher prevalence of thrombosis around the carotid web in the ipsilateral stroke group compared to the contralateral group (84.3% vs. 50.0%, P<0.001). However, there were no significant differences in the laterality, location, attachment site, length, thickness, angulation relative to the vessel wall, mobility with blood flow, and orientation relative to the flow direction of the carotid web between the two groups (all P>0.05). Conclusions This study demonstrated that thrombosis around the carotid web may be associated with ipsilateral ischemic stroke.